Evaluating the sources of funding for Algerian professional football clubs (Field study on first professional league football clubs) - لعجال , يحي; حشروف , أسامة (sports creativity, 2025)
The aim of the study was to evaluate the sources of funding for Algerian professional football clubs from the point of view of the marchers who practice within professional sports clubs, and to achieve this the study was conducted on a sample of (15) professional clubs with a total of (75) marchers from each professional sports club, and the researcher followed the descriptive approach, and used a questionnaire form as a tool for collecting data, and the results showed that the degree of evaluation of the sources of funding of Algerian professional football clubs is medium and there is agreement in the views of workers in the views of workers in Algerian professional clubs in the degree of evaluating sources of funding despite